PENGARUH PERSEPSI PESERTA DIDIK DALAM PENGELOMPOKAN KELAS TERHADAP HASIL BELAJAR DAN ETIKA PERGAULAN - Alisa Widiya Lestari; Sulasfiana Alfi Raida (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This research to obtain information and analyze data about the effect of students 'perceptions in class grouping on learning outcomes and the students' social ethics in the subject of the moral code of class VIII MTs Ma'ahid Kudus. This research uses a quantitative approach, which was carried out at MTs Ma'ahid Kudus Jl. K.H. Muhammad Arwani, Bakalan Krapyak Kaliwungu District, Kudus Regency. The population in studens of class VIII taken as many as 135 students by using purposive sampling technique. The results of the study show that: (1) The learning outcomes of the moral subjects of the VIII MTs Ma'ahid Kudus are included in the good category, which is at intervals (94-89). (2) The social ethics of students in class VIII MTs Ma'ahid Kudus is included in the good category, namely at intervals (50-54). (3) The influence between students 'perceptions in class grouping on students' cognitive learning outcomes in the moral subjects of the VIII grade at MTs Ma'ahid Kudus is 32%. (4) The influence between students 'perceptions in class grouping on the students' social ethics in the VIII moral subjects in MTs Ma'ahid Kudus is 37%.